Substitusi Tepung Ikan Dengan Tepung Cacing Tanah (Lumbricus rubellus) Terhadap Retensi Protein, dan Retensi Lemak, Pada Ikan Mas (Cyprinus carpio) - Nurhidayati, Melsa; Nikhlani, Andi; Pagoray, Henny (Universitas Batangahari Jambi, 2026)
This study aims to analyze protein retention and fat retention in common carp (Cyprinus carpio) fed formulated feed with substitutions of fishmeal and earthworm meal (L. rubellus), as well as to determine the best substitution ratio between fishmeal and earthworm meal (L. rubellus) in formulated feed for protein retention and fat retention in common carp (Cyprinus carpio). The study used a completely randomized design (CRD) consisting of four treatments and three replications. The treatments in this study were differences in the doses of fishmeal and earthworm meal given to the carp at different doses, namely PA (100% fishmeal and 0% earthworm meal), PB (75% fishmeal and 25% earthworm meal), PC (50% fishmeal and 50% earthworm meal), and PD (25% fishmeal and 75% earthworm meal). The main parameters observed included protein retention, fat retention, and absolute biomass weight growth, while supporting parameters such as water quality were measured periodically. The results showed that substituting fishmeal with earthworm meal had a significant effect (P